Prenatal Glucocorticoid-Exposed Infants Do Not Show an Age-Typical Fear Bias at 8 Months of Age – Preliminary Findings From the FinnBrain Birth Cohort Study - Kataja, Eeva-Leena; Rodrigues, Ana João; Scheinin, Noora M.; Nolvi, Saara; Korja, Riikka; Häikiö, Tuomo; Ekholm, Eeva; Sousa, Nuno; Karlsson, Linnea; Karlsson, Hasse (Frontiers in Psychology, 2021)
Synthetic glucocorticoids (sGC) are frequently administered to pregnant women at risk for preterm delivery to promote fetal lung maturation. Despite their undeniable beneficial effects in lung maturation, the impact of these hormones on developing brain is less clear. Recent human studies suggest that emotional and behavioral disorders are more common among sGC-exposed vs. non-exposed children, but the literature is sparse and controversial. We investigated if prenatal sGC exposure altered fear bias, a well-established infant attention phenotype, at 8-months. We used eye tracking and an overlap paradigm with control, neutral, happy, and fearful faces, and salient distractors, to evaluate infants’ attention disengagement from faces, and specifically from fearful vs. neutral and happy faces (i.e., a fear bias) in a sample (N=363) of general population from the FinnBrain Birth Cohort Study. sGC exposed infants (N=12) did not differ from non-exposed infants (N=351) in their overall probability of disengagement in any single stimulus condition. However, in comparison with non-exposed infants, they did not show the age-typical fear bias and this association remained after controlling for confounding factors such as prematurity, gestational age at birth, birth weight, sex, and maternal postnatal depressive symptoms. Prenatal sGC exposure may alter emotional processing in infants. The atypical emotion processing in turn may be a predictor of emotional problems later in development. Future longitudinal studies are needed in order to evaluate the long-term consequences of sGC exposure for the developing brain.